Pathways between soil moisture and precipitation in southeastern South America - Ruscica, Romina (2014)
Southeastern South America (SESA) is found to be the main hot spot of soil moisture?evapotranspiration coupling of South America during a dry summer. However, only its eastern part is a soil moisture?precipitation hot spot. Pathways between soil moisture and precipitation are evaluated through studying the coupling of soil moisture with surface and boundary layer variables. The outcome suggests that both the moist static energy and its vertical gradient are important for the development of precipitation, as a result of the total surface heat fluxes that are affected by soil moisture only in the eastern part of SESA.